WHAT LEADS GUESTS TO SATISFACTION AND LOYALTY IN UAE FIVE-STAR HOTELS? AHP ANALYSIS TO SERVICE QUALITY DIMENSIONS - Alzoubi, Haitham M.; Vij, Mohit; Vij, Anu; Hanaysha, Jalal Rajeh (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2021)
The hospitality industry has witnessed impressive growth in the recent past. However, this has also led to fierce competition resulting in an enhanced focus on customer satisfaction. This study investigates and identifies critical service dimensions for five-star hotels in the United Arab Emirates (UAE). The objective of the study is to examine the intricacies of customer satisfaction and loyalty with regard to service quality in the five-star hotels of UAE. Following a quantitative and empirical approach, the data was collected by a structured questionnaire and tested on Analytic Hierarchy Process (AHP). Results support the impact of service quality dimensions on both Customer Satisfaction and Customer Loyalty. The "Personal Contact” dimensions (Responsiveness and Empathy) and the "Service Performance” dimensions (Reliability and Assurance) were found to be a significant factor impacting the perception of the hotels’ guests towards Service Quality. The findings are useful particularly to the hotel industry to analyze the gaps in service quality and thereafter put more efforts into developing appropriate strategies for achieving customer satisfaction and customer loyalty.